Research on the post-weld explosive hardening of AA7075-T651 friction stir welded butt joints - Kosturek, Robert; Lewczuk, Rafał; Torzewski, Janusz; Wachowski, Marcin; Słabik, Piotr; Maranda, Andrzej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
In this paper, the post-weld explosive hardening of a 5 mm AA7075-T651 plate welded via FSW was performed. To investigate the possibility of increasing FSW joint mechanical properties, the welded plate was explosively treated with four various explosive materials (ammonal, emulsion explosive, FOX-7, and PBX) in two different hardening systems. As part of the investigation, the observations of the surface and macrostructure of the treated plates were described. The obtained microhardness distribution allowed us to register the increase in hardness of the SZ up to 6%, but no increase in hardness of the LHZ was reported. In most cases, the influence of explosive treatment on the mechanical properties of the welded joint was disadvantageous as ultimate tensile strength and ductility were reduced. The only positive effect which was observed is the increase in the value of yield strength up to 27% corresponding to 77 MPa, achieved by explosive materials with detonation velocity below 3000 m/s.